THE EFFECT OF WORK MOTIVATION AND WORK DISCIPLINE ON HUMAN RESOURCES OF LAMPUNG POLICE EMPLOYEE PERFOMANCE - David Ariswandy; Refi Arioen (University of Sang Bumi Ruwa Jurai, 2021)
The research objective in this thesis is to examine the effect of work motivation and work discipline on the Performance of the Lampung Regional Police HR Bureau members. This study used a population research method with a total of 51 respondents. The analysis is used using quantitative analysis and data processing using the SPSS program. The results showed that work motivation affects the Performance of the members with an influence contribution of 84.3%. Furthermore, Work Discipline also affects the Performance of members with an influence contribution of 87%. Taken together, there is an influence between Work Motivation and Work Discipline on Member performance. The amount of influence of the two variables X1 and X2 on Y is 89.7%, the remaining 10.3% is influenced by other variables outside of this study.